Peranan Kepolisian Dalam Menanggulangi Tindak Pidana Pencucian Uang (Studi Di Kepolisian Daerah Sumatera Utara) (LPPM Universitas HKBP Nommensen, 2022)
This study aims to determine and understand the roleof the police in dealing with money laundering. -views inbuilding legal arguments for data collection Researchersalso conduct field studies (Field Research) by conductingDirect Interviews conducted at the North Sumatra Regional Police (Poldasu) The role of the police incarrying out their duties as law enforcement there areobstacles, namely good from internal and external factors Therole of the police in tackling the crime of moneylaundering includes pre-emptive measures. preventive and repressivemeasures This regulation related to money laundering isbased on Law Number 8 of 2010 concerning the preventionand eradication of money laundering in Indonesia, PenalEfforts (repressive) and non-penal (preventive) measuresthat the Police can undertake to tackling the crime of moneylaundering in the context of carrying out its duties as aState apparatus that maintains public security andorder, enforces the law, and protects. Protecting andserving the community is based on Law Number 2 of 2002concerning the Indonesian National Police